Indigenous languages ​​and the historiography of Latin America - Durston, Alan (2013)
The historiography on Latin America is increasingly cognizant of the fact that the post-conquest development of indigenous languages cannot be understood in terms of a linear process of decline, and that there are valuable sources in these languages from unexpected times and places. An important segment of the historiography on colonial Mexico has long made intensive use of indigenous-language sources, and indigenous languages are beginning to appear on the historiographical radar elsewhere. This article surveys the treatment of indigenous languages and indigenous-language sources in the historiographies on Mexico, Peru, and Paraguay. It argues that the most promising new trends in the field include greater attention to the social history of language, to the use of indigenous languages by non-Indians, and to their use in nation-building processes.